2017
DOI: 10.20473/jn.v12i1.4028
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Open Defecation Behavior Among School-Age Children in West Lombok

Abstract: Introduction: Open defecation behavior is one cause of poor sanitation, which can lead to various diseases. Open defecation behavior related with cultural factors that become a habit in the daily life in a society which was then followed by their children. This study aimed to analyze factors related to the parental behavior of open defecation in school-age children based on the theory of transcultural nursing in Marce, Sedau Community Health Center Area, West Lombok Indonesia. Methods: This was a descriptive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…In a similar study to assess factors related to OD behavior among school-age children in West Lombok, Indonesia, most of the respondents with low-income levels did not have a latrine facility at their homes as they cannot afford the cost of construction. 13 According to KNBS and SID report, 2013, only 6% of the population in Turkana County works for pay and is ranked the last and is the poorest county in Kenya. 6 Households with low-income levels will often place a lower priority on sanitation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a similar study to assess factors related to OD behavior among school-age children in West Lombok, Indonesia, most of the respondents with low-income levels did not have a latrine facility at their homes as they cannot afford the cost of construction. 13 According to KNBS and SID report, 2013, only 6% of the population in Turkana County works for pay and is ranked the last and is the poorest county in Kenya. 6 Households with low-income levels will often place a lower priority on sanitation.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from a similar study among school-age children in West Lombok, Indonesia, reported that such communities are often comfortable defecating in the open even if such situations are uncertain. 13 As a result, such communities are not too oriented to any form of regulations. A combination of fines, shaming, and withholding of community benefits may be considered as successful sanitation elements that may promote latrine construction as well as its usage among such communities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Education is a prominent factor for those who pay critical attention to preserve their health. However, every of which will be ended up in vain should the intention is not accompanied with awareness and willingness to commence change in their undertakings (Makhfudli, Rachmawati, and Andini, 2017).…”
Section: Knowledgementioning
confidence: 99%